Kinerja Pegawai dalam Perspektif Work Environment dan Work-Life Balance: Kajian Literatur tentang Peran Kepuasan Kerja - Yulia Fitriana; Khuzaini; Zakky Zambrudi; Syahrial Shaddiq; Prasetyo Yuli Usaid (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze employee performance from the perspectives of work environment and work-life balance, with job satisfaction as an intervening variable through a literature review approach. The study is based on ten empirical articles obtained from open-access scientific journals, which were selected based on their relevance to the research variables. Data were analyzed using a descriptive method to identify patterns of relationships and inconsistencies among previous studies. The findings indicate that work-life balance consistently has a positive and significant effect on job satisfaction, which in turn contributes to improved employee performance. Meanwhile, the work environment generally influences job satisfaction positively, but its direct effect on employee performance shows inconsistent results. Job satisfaction plays a mediating role, although its effect is not always significant across studies. These findings suggest that employee performance is influenced by a complex interaction of organizational and psychological factors, and organizations are encouraged to enhance both work-life balance and a supportive work environment to improve job satisfaction and performance